Open-source automated insulin delivery: international consensus statement and practical guidance for health-care professionals. Issue 1 (January 2022) - Braune, Katarina; Lal, Rayhan A; Petruželková, Lenka; Scheiner, Gary; Winterdijk, Per; Schmidt, Signe; Raimond, Linda; Hood, Korey K; Riddell, Michael C; Skinner, Timothy C; Raile, Klemens; Hussain, Sufyan; et al.
Summary: Open-source automated insulin delivery systems, commonly referred to as do-it-yourself automated insulin delivery systems, are examples of user-driven innovations that were co-created and supported by an online community who were directly affected by diabetes. Their uptake continues to increase globally, with current estimates suggesting several thousand active users worldwide. Real-world user-driven evidence is growing and provides insights into safety and effectiveness of these systems. The aim of this consensus statement is two-fold. Firstly, it provides a review of the current evidence, description of the technologies, and discusses the ethics and legal considerations for these systems from an international perspective. Secondly, it provides a much-needed international health-care consensus supporting the implementation of open-source systems in clinical settings, with detailed clinical guidance. This consensus also provides important recommendations for key stakeholders that are involved in diabetes technologies, including developers, regulators, and industry, and provides medico-legal and ethical support for patient-driven, open-source innovations.